1925
DOI: 10.1002/bjs.1800124807
|View full text |Cite
|
Sign up to set email alerts
|

The surgical treatment of cardiospasm

Abstract: GENERAL CONSIDERATIONS.THE most unsatisfactory chapter in the surgery of to-day is that of the treatinent of oesophageal obstruction. The grave discomfort of being unable to swallow, the frequency with which the obstruction is due to carcinoma, the inaccessibility of the oesophagus, and the consequent unsatisfactory results of surgical treatment, make this the most dreaded of all diseases. Fortunately therc is quite a definite proportion of cases where the obstruction is not due to carcinoma and can be complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1926
1926
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Achalasia was more fully described by Ziemssen, Zenker, and Mikulicz in the 19th century [6,20]. Since that time, various nonsurgical therapies have been employed to treat this disease, including esophageal dilation, oral nitrates, calcium channel blockers, and the injection of botulinum toxin directly into the lower esophageal sphincter.…”
mentioning
confidence: 98%
“…Achalasia was more fully described by Ziemssen, Zenker, and Mikulicz in the 19th century [6,20]. Since that time, various nonsurgical therapies have been employed to treat this disease, including esophageal dilation, oral nitrates, calcium channel blockers, and the injection of botulinum toxin directly into the lower esophageal sphincter.…”
mentioning
confidence: 98%
“…Freeman 44 frequency of muscle atrophy in the vicinity of fibrosis between the two layers, although the usual interpretation is that such atrophy is merely a late response to esophageal retention, following a period of compensatory muscular hypertrophy. 45,46 Goldblum et al 47 showed a secondary degeneration and fibrosis in 29/42 esophageal resectates with achalasia. Our own recent analyses of biopsies taken from the high pressure zone of the distal esophagus in patients undergoing surgery for achalasia revealed an association between the duration of symptoms prior to the operation and the degree of fibrosis.…”
Section: Persistent Achalasia or Early Recurrencementioning
confidence: 98%
“…It was Sir James Walton (1925) who divided cardiospasm into two clinical types, the painful and the painless. It is probable that spasm may be the cause of the pain, for oesophagitis and peptic ulceration cannot be demonstrated in all these cases.…”
Section: Clinical Featuresmentioning
confidence: 99%